Mechanisms of Congenital Heart Disease Caused by NAA15 Haploinsufficiency. Issue 8 (9th February 2021) - Ward, Tarsha; Tai, Warren; Morton, Sarah; Impens, Francis; Van Damme, Petra; Van Haver, Delphi; Timmerman, Evy; Venturini, Gabriela; Zhang, Kehan; Jang, Min Young; Willcox, Jon A.L.; Haghighi, Alireza; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: NAA15 (N-alpha-acetyltransferase 15) is a component of the NatA (N-terminal acetyltransferase complex). The mechanism by which NAA15 haploinsufficiency causes congenital heart disease remains unknown. To better understand molecular processes by which NAA15 haploinsufficiency perturbs cardiac development, we introduced NAA15 variants into human induced pluripotent stem cells (iPSCs) and assessed the consequences of these mutations on RNA and protein expression. Objective: We aim to understand the role of NAA15 haploinsufficiency in cardiac development by investigating proteomic effects on NatA complex activity and identifying proteins dependent upon a full amount of NAA15. Methods and Results: We introduced heterozygous loss of function, compound heterozygous, and missense residues (R276W) in iPSCs using CRISPR/Cas9. Haploinsufficient NAA15 iPSCs differentiate into cardiomyocytes, unlike NAA15 -null iPSCs, presumably due to altered composition of NatA. Mass spectrometry analyses reveal ≈80% of identified iPSC NatA targeted proteins displayed partial or complete N-terminal acetylation. Between null and haploinsufficient NAA15 cells, N-terminal acetylation levels of 32 and 9 NatA-specific targeted proteins were reduced, respectively. Similar acetylation loss in few proteins occurred in NAA15 R276W induced pluripotent stem cells. In addition, steady-state protein levels of 562 proteins were altered in both null and haploinsufficient NAA15 cells; 18 were ribosomal-associated proteins. At least 4 proteins were encoded by genes known to cause autosomal dominant congenital heart disease. Conclusions: These studies define a set of human proteins that requires a full NAA15 complement for normal synthesis and development. A 50% reduction in the amount of NAA15 alters levels of at least 562 proteins and N-terminal acetylation of only 9 proteins. One or more modulated proteins are likely responsible for NAA15-haploinsufficiency mediated congenital heart disease. Additionally, genetically engineered induced pluripotent stem cells provide a platform for evaluating the consequences of amino acid sequence variants of unknown significance on NAA15 function.